Pemanfaatan Framework Laravel Dan Framework Bootstrap Pada Pembangunan Aplikasi Penjualan Hijab Berbasis Web - Desma Alpina; Harry Witriyono (Jurnal Media Infotama, 2022)
Competition Between Stores Has Become Fierce Because They Have Implemented Offline And Online Sales. Online Sales Have Become A Transaction Medium Where Buyers Do Not Have To Meet The Seller To See The Product And Make A Purchase. The Current Rise Of The Hijrah Trend Has A Direct Impact On Increasing Sales Of Hijabs Among Young People. Coupled With The Very Diverse Indonesian Hijab Culture, There Are Many Types, Models And Designs Of Beautiful Hijabs Which Are Not Only Used To Cover The Private Parts But Have Become One Of The Current Fashion Items. One Framework That Helps In Building Sales Applications Is Laravel. Laravel Is An Open Source Programming Framework That Is Used By Many Developers From All Over The World. Laravel Is Also A Framework That Can Help Developers Maximize The Use Of PHP In The Website Development Process. Apart From That, Laravel Also Has Several Superior Features, Such As Template Engine, Routing, And Modularity. The Laravel Framework Has Advantages In File Structure And Coding Compared To Ordinary Native PHP. The Laravel Framework Has A Migrate Function So It Is Easier To Manage The Database. The Laravel Framework Has A Templating Engine That Can Help Build The Front End More Efficiently With The Blade Function Provided By Laravel. The Bootstrap Framework With CSS Makes The Application Look Nicer And Neater. The Application That The Author Has Built Is Not Perfect So There Are Still Many Shortcomings, Both In Terms Of Appearance And More User Friendly Facilities. Apart From That, This Application Also Has Shortcomings In The Payment Section Which Is Still Manual Due To The Author's Limited Knowledge So He Has Not Been Able To Create A Payment Function That Is Integrated With Virtual Money Such As Gopay, Dana Or OVO.